1997
DOI: 10.1105/tpc.9.1.97
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Opaque2 changes diurnally and impacts its DNA binding activity.

Abstract: P i e t r o Ciceri,a.l E l i s a b e t t a Gianazza,b B a r b a r a Lazzari,a G u i d o Lippoli,a A n n a m a r i a Genga,a Gisela Hoschek,c R o b e r t J. Schmidt,c a n d A n g e l o Viottiag2 a lstituto Biosintesi Vegetali, Consiglio Nazionale delle Ricerche, Via Bassini 15, 1-201 33 Milan, ltaly lstituto di Scienze Farmacologiche, Universita degli Studi di Milano, Via Balzaretti 9, 1-201 33 Milan, ltalyDepartment of Biology and Center for Molecular Genetics, University of California at San Diego, La Jolla, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 51 publications
3
52
1
Order By: Relevance
“…Another plant bZIP, Opaque-2 from maize, is likely phosphorylated by casein kinase II. Diurnal oscillation between hyper-and hypophosphorylated isoforms of Opaque-2 results in accumulation of the phosphorylated isoform during the night, and the DNA binding potential of the phosphorylated form is diminished (Ciceri et al, 1997). With regard to GRAS proteins, phosphorylation and dephosphorylation states of the DELLA subfamily are correlated with their stability, plant growth repressive activity, and gibberellic acid (GA)-induced degradation (Hussain et al, 2005;Itoh et al, 2005); reversible phosphorylation is required for the plant stress-induced response of tobacco (Nicotiana tabacum) GRAS1 (Czikkel and Maxwell, 2007); rice (Oryza sativa) CIGR1 and CIGR2 (for Chitininducible gibberellin-responsive protein) are induced by GA signals, depending on both phosphorylation and dephosphorylation events (Day et al, 2004).…”
Section: Intrinsic Disorder Facilitates Phosphorylationmentioning
confidence: 99%
“…Another plant bZIP, Opaque-2 from maize, is likely phosphorylated by casein kinase II. Diurnal oscillation between hyper-and hypophosphorylated isoforms of Opaque-2 results in accumulation of the phosphorylated isoform during the night, and the DNA binding potential of the phosphorylated form is diminished (Ciceri et al, 1997). With regard to GRAS proteins, phosphorylation and dephosphorylation states of the DELLA subfamily are correlated with their stability, plant growth repressive activity, and gibberellic acid (GA)-induced degradation (Hussain et al, 2005;Itoh et al, 2005); reversible phosphorylation is required for the plant stress-induced response of tobacco (Nicotiana tabacum) GRAS1 (Czikkel and Maxwell, 2007); rice (Oryza sativa) CIGR1 and CIGR2 (for Chitininducible gibberellin-responsive protein) are induced by GA signals, depending on both phosphorylation and dephosphorylation events (Day et al, 2004).…”
Section: Intrinsic Disorder Facilitates Phosphorylationmentioning
confidence: 99%
“…For example, an increase in bZIP family abundance corresponded to increases in bZIP phosphorylation, whereas the opposite pattern was observed for the ARF family. Considering that the DNA binding activity of OPAQUE2 (a maize bZIP) and ARF2 (in Arabidopsis) is abolished by hyperphosphorylation (41,42), our TF phosphorylation data may be used to infer TF activities during development.…”
Section: −3mentioning
confidence: 99%
“…In particular, reversible phosphorylation is a common mechanism for the selective regulation of transcription factors. In higher plants, the phosphorylation of transcription factors might be an important mechanism for the selective control of gene expression in response to environmental signals (Wellmer et al 1999;Klimczak et al 1995;Ciceri et al 1997;Kircher et al 1998;Zhou et al 1997). In this study, SBZ1 was phosphorylated by a soybean cell extract in vitro ( Figure 5A).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have suggested that the activities of plant transcription factors can also be modulated by phosphorylation. Phosphorylation affects the affinities of some transcription factors for their DNA targets in vitro (Klimczak et al 1995;Ciceri et al 1997;Hardtke et al 2000). We examined, therefore, whether phosphorylation has any influence on the affinity of SBZ1 for the binding sequence ( Figure 6).…”
Section: In Vitro Phosphorylation Of Sbz1mentioning
confidence: 99%